The Interaction Between Long Non-coding RNA HULC and MicroRNA-622 via Transfer by Extracellular Vesicles Regulates Cell Invasion and Migration in Human Pancreatic Cancer - Takahashi, Kenji; Koyama, Kazuya; Ota, Yu; Iwamoto, Hidetaka; Yamakita, Keisuke; Fujii, Satoshi; Kitano, Yohei (Frontiers in Oncology, 2020)
Although non-coding RNAs (ncRNAs) are involved in disease pathogenesis, their contributions to pancreatic ductal adenocarcinoma (PDAC) remain unclear. Recently, the interrelationship between two classes of ncRNA, long non-coding RNAs (lncRNAs) and microRNAs (miRNAs), has been reported to contribute to the epigenetic regulation of gene expression in several cancers. Moreover, some ncRNAs can be transferred by extracellular vesicles (EVs) from their donor cells to recipient cells. We previously verified that lncRNA HULC is upregulated in PDAC cells and the intercellular transfer of HULC by EVs can promote PDAC cell invasion and migration through the induction of epithelial–mesenchymal transition (EMT). Therefore, we identified the miRNA that could target HULC and investigated the functional contributions of the miRNA–HULC interaction and EV transfer of miRNA to the EMT pathway in human PDAC. Microarray analysis revealed 187 miRNAs that were decreased to < 0.87-fold in Panc-1 cells treated with TGF-β compared to the control. Of these, miR-622 was predicted to target HULC by bioinformatics analysis. miR-622 expression was significantly reduced by TGF-β in a panel of PDAC cells. Overexpression of miR-622 using a miRNA mimic significantly decreased HULC expression, increased E-cadherin expression, and decreased Snail, N-cadherin, and vimentin expression. Moreover, miR-622 overexpression significantly reduced cell invasion and migration whereas inhibition of miR-622 increased HULC expression and promoted EMT signaling, invasion, and migration of PDAC cells. Furthermore, incubation with miR-622-overexpressing EVs could transfer miR-622, which significantly elevated miR-622 expression and decreased cell invasion and migration via inhibition of the EMT pathway in recipient PDAC cells. These results provide mechanistic insights into the development of PDAC by demonstrating that miR-622, as a miRNA downregulated by TGF-β, could target HULC and suppress invasion and migration by inhibiting EMT signaling via EV transfer. These observations may identify EV-encapsulated miRNA as a novel therapeutic target for human PDAC.